The Relation Between Classroom Adversity and Students' Problem Behavior as a Function of Teachers' Emotional Support. - Granger, Kristen L.; Chow, Jason C.; McLean, Leigh; Vallarta, Natalie; Dear, Emma; Sutherland, Kevin S. (Behavioral Disorders, 2024)
The purpose of this study was to examine the relation between teachers' reports of classroom adversity, a measure of classroom hardship, and student problem behavior in a sample of students with or at risk of emotional/behavioral disorders. We also examined the extent to which this relation varied as a function of multiple domains of classroom quality. A series of multiple regression models, adjusting for the nesting of students within classrooms, were conducted. Models revealed a significant effect of the interaction between classroom adversity and classroom emotional support on teachers' reports of student problem behaviors. This effect indicated that in low-adversity classrooms, teachers differed in their reports of students' problem behaviors depending on their level of emotional support. In high-adversity classrooms, however, teachers' reports of students' problem behaviors were relatively similar regardless of their level of emotional support. Findings suggest classroom adversity is likely an important contextual factor to consider when examining student outcomes and that teacher emotional support may mitigate the influence of classroom adversity. We conclude with a discussion of the implications of this work for research and practice.